2016
DOI: 10.1161/hypertensionaha.115.06300
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Corin Levels Indicate Early Systolic Dysfunction Before Increases of Atrial Natriuretic Peptide/B-Type Natriuretic Peptide and Heart Failure Development

Abstract: Dilated cardiomyopathy is a major cause of heart failure that affects millions. Corin cleaves and biologically activates pro-atrial natriuretic peptide (pro-ANP) and pro-B-type natriuretic peptide (pro-BNP). High corin levels reduce the development of systolic dysfunction and heart failure in experimental dilated cardiomyopathy. Yet, patients with significant heart failure unexpectedly show low corin levels with high plasma ANP/BNP levels. Therefore, we examined the relationship between cardiac corin expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(108 citation statements)
references
References 32 publications
7
99
0
Order By: Relevance
“…A failure of coordinated expression of cardiac levels of corin and the proNPs may lead to reduced activation of proNPs and functional dysregulation of the NP system in HF . This may contribute to the decreased cleavage and elevated levels of unprocessed ANPs in patients with HF, lending support to the idea that HF is a corin‐deficient state in which low corin levels may have a causative role ( Figure ) . This assumption is further supported by the findings of a recent experimental study, which showed that corin overexpression improved cardiac function, reduced pulmonary oedema, and increased survival in a mouse model of dilated cardiomyopathy .…”
Section: Global Left Atrial Failure In Heart Failurementioning
confidence: 60%
See 1 more Smart Citation
“…A failure of coordinated expression of cardiac levels of corin and the proNPs may lead to reduced activation of proNPs and functional dysregulation of the NP system in HF . This may contribute to the decreased cleavage and elevated levels of unprocessed ANPs in patients with HF, lending support to the idea that HF is a corin‐deficient state in which low corin levels may have a causative role ( Figure ) . This assumption is further supported by the findings of a recent experimental study, which showed that corin overexpression improved cardiac function, reduced pulmonary oedema, and increased survival in a mouse model of dilated cardiomyopathy .…”
Section: Global Left Atrial Failure In Heart Failurementioning
confidence: 60%
“…Experimental studies have demonstrated that intravenous infusion of atrial extracts from normal rats incites a rapid and potent diuretic and vasodilating response, whereas, such a response is not observed when atrial extracts from hamsters with congestive HF are used . Moreover, lack of coordination, or dyssynchrony, has been recently shown in cardiac corin and proANP/proBNP expression with declining systolic function in an experimental mouse model of dilated cardiomyopathy . A failure of coordinated expression of cardiac levels of corin and the proNPs may lead to reduced activation of proNPs and functional dysregulation of the NP system in HF .…”
Section: Global Left Atrial Failure In Heart Failurementioning
confidence: 99%
“…A growing body of evidence in humans and experimental models suggests that corin, a cardiac transmembrane II serine protease, plays diagnostic, prognostic, and protective roles in DCM and HFrEF development [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Cardiac corin is co-expressed with pro-atrial natriuretic peptide (pro-ANP) and localized on the cardiomyocyte surface [25,26], where it cleaves/activates secreted pro-ANP generating biologically active ANP peptides.…”
Section: Introductionmentioning
confidence: 99%
“…ProANP is processed into NT-proANP and ANP by the cardiac serine protease et al reported that decreased corin levels promoted the transition from the early to late stage of HF with impaired proANP processing in a dilated cardiomyopathy (DCM) model in mice. 49 When considered together, these studies suggest that corin may play a role in controlling the HT and cardiac hypertrophy that proceed to the development of HF, specifically through proANP processing. There are only a few studies suggesting possible therapeutic strategies regarding corin to facilitate proANP processing to ANP.…”
Section: Anp Molecular Forms Processing and Degradationmentioning
confidence: 97%